Atividade enzimática extracelular de leveduras isoladas da fermentação do cacau - Silva, Marcielle dos Santos (2011)
The enzymes have peculiar characteristics, such as specificity, diversity and capacity of large scale production. Moreover, its potential biotechnology is great, being one of them the obtaining of products through of the fermentative process. The present work had as objective the investigating the production of proteases, lipases, amylases, cellulases, pectinases and fosfolipases secreted by yeasts isolated from cocoa’s fermentation. The methodology used initially was of the cup plate, followed of the titrimetric tests for lipases and spectrophotometric tests for pectinases and proteases. From of 70 yeasts 56 (80%) were positive to the secretion of at least one of the enzymes studied in tests made on board. Thirteen strains (18%) were positive for amylase, 35 (50%) for cellulases, 11 (15%) for fosfolipases; 12 (17%) to pectinase and (17%) for protease. Us tests on board for the lipases the substrate palm oil was what presented largest number of strains able to use it, being 24 (34%) positive yeast for the lipase activity, 10 (14%) were positive for castor oil and 8 (11%) for cocoa butter. For the titrimetric tests all the yeasts were positive in the three substrates (palm oil, castor oil and cocoa butter) being the best results obtained for the yeasts tests with palm oil. In the quantitative spectrophotometric tests, 62 (88%) of the yeasts were positive for protease and 68 (97%) to pectinases. This study demonstrated that the microrganisms tested represent a potential source of extracellular enzymes of industrial and biotechnological interest.